STUDI KONDISI LINGKUNGAN DESA NIKEL DAN KAITANNYA TERHADAP PEMANFAATAN RUANG KAWASAN TEPIAN AIR DANAU MATANO - Amelia , Afriyanti Nur; Aksa , Nursyam; Albab, Nurul Istiqamah Ulil (Journal of Spatial Transformation, 2025)
Matano Lake, located in East Luwu Regency, South Sulawesi, is a water area with significant tourism and ecosystem potential. However, the development of settlements in the waterfront area has caused worrying environmental impacts, such as water pollution and degradation of ecosystem quality. This study aims to formulate guidelines for sustainable spatial use in the Matano Lake shoreline area by considering the environmental impacts of local community activities. The methodology used is a qualitative and quantitative approach (mixed methods) through field surveys, interviews, and satellite image interpretation. Environmental analysis was carried out using scoring and weighting techniques based on environmental quality parameters, including building density, infrastructure conditions, and waste management systems. The results of the analysis show that the environmental quality in the Matano Lake shoreline area is in the moderate category, indicating the need for improvements in the management of residential areas, drainage systems, and protection of the lake ecosystem. Based on the results of the study, it is recommended to implement zoning policies, better waste management, and reorganization of residential areas as mitigation measures. These spatial use guidelines are expected to maintain a balance between community needs and the preservation of the Matano Lake ecosystem.